Abide Sitesi as Innovative Approach to Build-and-Sell Housing Production in Post-World War II Istanbul - Özlem Balci Öztürk; Burak Öztürk (Prostor)
Yapsatçılık, meaning build-and-sell, is a capital-free model based on apartment sharing between landholders and developers that became widespread among the post-war housing production methods in Turkey. The Abide Sitesi settlement in Istanbul’s Mecidiyeköy district is the focus of this study, as it is the first large-scale initiative of the build-and sell method and, contrary to all criticism, proves that the method could produce successful practices. Prior to this, Kemal Ahmet Aru prepared a garden-city master plan for the same land in 1955, but this plan was never realized. After various legal regulations made it possible to open this land for settlement, in 1975, Yaşat Inc. started the Abide Sitesi project. This study examines the transformation effects of urban development dynamics on the built environment through the Abide Sitesi case. In this context, Abide Sitesi offers an in-depth analysis of project-to-construction processes, housing sale policies, and architectural characteristics. The study benefits from municipal and newspaper archives, and the theoretical framework is supported by site analysis and photographic documentation.